2013
DOI: 10.1210/jc.2012-3676
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian Hormone Levels Are Strongly Associated With Live-Birth Rates After Assisted Reproduction

Abstract: Context:Previous studies have suggested that antimü llerian hormone (AMH) levels are positively associated with in vitro fertilization (IVF) outcome through their relationship with oocyte yield and not by reflecting oocyte or embryo quality. Objective:The aim was to investigate whether AMH levels are associated with pregnancy and live-birth rates and whether the results may also reflect qualitative aspects of oocytes and embryos. Design:The study was a prospective cohort study between April 2008 and June 2011.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
3
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 39 publications
8
104
3
7
Order By: Relevance
“…The two markers are strongly related to the quantitative aspect of ovarian reserve; hence a low AMH and/or AFC are highly indicative of possible low number of growing follicles and oocyte following ovarian stimulation. Moreover, both low AMH and AFC have been associated to reduced pregnancy and live birth following IVF independent of age [35][36][37][38][39][40][41]. This may indicate some relationship between quantity and quality of oocytes, with a The present study because of its retrospective design has relevant limitations, including a biased selection of women recruited for the study.…”
Section: Discussionmentioning
confidence: 85%
“…The two markers are strongly related to the quantitative aspect of ovarian reserve; hence a low AMH and/or AFC are highly indicative of possible low number of growing follicles and oocyte following ovarian stimulation. Moreover, both low AMH and AFC have been associated to reduced pregnancy and live birth following IVF independent of age [35][36][37][38][39][40][41]. This may indicate some relationship between quantity and quality of oocytes, with a The present study because of its retrospective design has relevant limitations, including a biased selection of women recruited for the study.…”
Section: Discussionmentioning
confidence: 85%
“…AMH is an established marker of OR, and previous work showed its value in predicting the ovarian response to COS [5,19]. More recently, the accuracy of AMH in predicting live birth was tested by independent groups: some data showed that AMH could be used as a prognostic factor [20][21][22], but its predictive value at low or very low concentrations was not clearly clarified. In fact, some authors reported acceptable results in terms of clinical pregnancies even in patients with very low AMH levels (0.1-0.35) whereas others suggested their exclusion from IVF treatment due to a very poor prognosis [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, basal follicle-stimulating hormone (fsh) has been the standard evaluation of ovarian reserve and a simple means to screen patients for diminished response and poor outcome with ivf 55 . Antimüllerian hormone (amh) is proving to be the most predictive for ovarian response to exogenous gonadotropins and for pregnancy outcome, and also the most versatile in such patients [56][57][58] . Antimül-lerian hormone is detectable at all ages and, unlike fsh, is stable throughout the menstrual cycle; it can therefore be assessed at the time of presentation.…”
Section: Assessment Of the Young Cancer Patientmentioning
confidence: 99%